Relasi Makna Orang Kafir dan Muttaqȋn dalam Islam - Sihabussalam Sihabussalam (JURNAL INDO-ISLAMIKA, 2011)
This paper will explain the relation of eating infidels and pious people in Islam. This research is a qualitative research using Charles Sanders Pierce's semiotic approach. The data used in this paper is sourced from books, journals, and also other literature that is relevant to the theme of the writing.